Myoclonus-dystonia: Distinctive motor and non-motor phenotype from other dystonia syndromes. (December 2019) - Timmers, Elze R.; Smit, Marenka; Kuiper, Anouk; Bartels, Anna L.; van der Veen, Sterre; van der Stouwe, A.M. Madelein; Santens, Patrick; Bergmans, Bruno; Tijssen, Marina A.J.
Abstract: Background: Myoclonus-dystonia (M-D) due to a pathogenic variant of SGCE is an autosomal dominant inherited movement disorder. Apart from motor symptoms, psychiatric disorders are highly prevalent in patients with M-D. Previous studies suggest, but never tested directly, that the type of psychiatric disorder differs between dystonia syndromes, probably related to disease specific pathology. Little is known about other non-motor symptoms (NMS) in M-D. Here, we systematically study NMS in M-D in direct comparison to other types of dystonia and healthy controls. Methods: Standardized questionnaires were used to assess type and severity of psychiatric co-morbidity, sleep problems, fatigue and quality of life. Results of M-D patients with a pathogenic variant of SGCE were compared to results of idiopathic cervical dystonia (CD) patients, dopa-responsive dystonia (DRD) patients with a pathogenic variant of GCH1 and controls. Results: We included 164 participants: 41 M-D, 51 CD, 19 DRD patients, 53 controls. Dystonia patients (M-D, CD and DRD) had an increased prevalence of psychiatric disorders compared to controls (56–74% vs. 29%). In M-D we found a significantly increased prevalence of obsessive-compulsive disorder (OCD) and psychosis compared to CD and DRD. All dystonia patients had more sleep problems (49–68% vs. 36%) and fatigue (42–73% vs. 15%) than controls. Compared to other dystonia subtypes, M-D patients reported less excessive daytime sleepiness and fatigue. Conclusion: Psychiatric comorbidity is frequent in all dystonia types, but OCD and psychosis are more common in M-D patients. Further research is necessary to elucidate underlying pathways. Highlights: Psychiatric comorbidity is frequent in all dystonia types. Obsessive compulsive disorder and psychosis are more common in Myoclonus-Dystonia. All dystonia patients had more sleep problems and fatigue than controls.